Gambel oak productivity and demography: an observational study of fundamental ecological characteristics in western Colorado - Brazenwood, Arian, author; Ex, Seth, advisor; Ocheltree, Troy, committee member; Sibold, Jason, committee member (Colorado State University. Libraries, 2020)
Gambel oak exhibits demographic and morphological variability across its range in the intermountain West. While broadly distributed, little is known about the basic ecological behavior of this species in Colorado ecosystems. We used an observational study to systematically describe variation in Gambel oak stand biometrics across a climatic moisture deficit (CMD) gradient on the Uncompahgre Plateau in western Colorado. Our analysis focused on parsing out differences in demographic characteristics including stand structure, age distribution, and productivity among varying levels of CMD with a 90-plot inventory capturing 2,312 tree measurements across a 200 mm range of CMD. To explore causal factors for variation in productivity, we used a mixed effects model derived from a systematic model selection process that identified predictors from a suite of biotic stand structure variables, and abiotic climatic and topographic variables. Metrics of tree size, stand density, and productivity varied systematically across the CMD gradient, where the driest sites had smaller trees, higher stand densities, and slower growth than wetter sites. In the driest sites, trees averaged 3.9cm of diameter at root collar (DRC) with mean densities of 9,000 trees per hectare contrary to the wettest sites where stems sizes averaged 7.5cm DRC with mean densities of 5,700 trees per hectare. However, regardless of variation in CMD, most stands were uneven-aged, as evidenced by uniform age proportions and ample regenerating cohorts of young stems across nearly all plots. Within a 60km2 study area across 500m of elevation difference, variables capturing climate and stand structure effects were the most predictive of productivity. A significant negative interaction between tree size and CMD indicates moisture limitation likely prevents trees on the driest sites sampled from attaining the larger sizes observed on wetter sites. Additionally, stands with high CMD were consistently younger than stands with low CMD, implying either more frequent stand-replacing disturbance in these locations or recent colonization of new areas. The demographic characteristics across all CMD levels indicate stands naturally achieve a more heterogeneous structure following about a century of growth. This suggests that management promoting multi-cohort stand structures could accelerate transition from homogeneous thickets to heterogeneous old forests. Given the variable growth rates across the CMD range, this would likely be most successful on wetter sites.
Keywords: western Colorado; productivity; demography; Gambel oak